Effect of the BASC system and its perception on the operational improvement of a logistics services company - López Rodríguez, Mara del Rosario (2025)
The Business Alliance for Secure Commerce (BASC) management system is a strategy to strengthen the security and efficiency of companies in the logistics sector by preventing illegal activities such as smuggling and drug trafficking. The problem lies in the need to evaluate its impact on operational efficiency and security. Prior to its implementation, the company had deficiencies in traceability, regulatory compliance and security, and employees did not have a clear understanding of the impact of this system on these aspects. To assess this impact, a mixed methodology was used, combining a document review and a questionnaire structured in five key sections: general data, perception of safety, operational efficiency, regulatory compliance, and challenges and benefits of the system. The results indicate improvements in performance indicators: on-time deliveries increased from 88 % to 96 %, returns were reduced by 51,4 %, fleet downtime decreased by 43,7 %, and occupational accidents decreased by 59 %. These findings demonstrate the tangible benefits of BASC, constituting a benchmark for companies in the sector that seek to optimize their processes, strengthen their safety systems and improve regulatory compliance, contributing to a more competitive environment that strengthens trust with customers and employees.